Biomimetic supramolecular designs for the controlled release of growth factors in bone regeneration - Azevedo, Helena S. (2015)
The extracellular matrix (ECM) of tissues is an assembly of insoluble macromolecules that specifically interact with soluble bioactive molecules and regulate their distribution and availability to cells. Recapitulating this ability has been an important target in controlled growth factor delivery strategies for tissue regeneration and requires the design of multifunctional carriers. This review describes the integration of supramolecular interactions on the design of delivery strategies that encompass self-assembling and engineered affinity components to construct advanced biomimetic carriers for growth factor delivery. Several glycan- and peptide-based self-assemblies reported in the literature are highlighted and commented upon. These examples demonstrate how molecular design and chemistry are successfully employed to create versatile multifunctional molecules which self-assemble/disassemble in a precisely predicted manner, thus controlling compartmentalization, transport and delivery. Finally, we discuss whether recent advances in the design and preparation of supramolecular delivery systems have been sufficient to drive real translation towards a clinical impact.